Ranma 1/2. Vol. 4 - Takahashi, Rumiko, 1957- (Takahashi, Rumiko, 1957- Ranma nibunnoichi., 1995)
Chinese Amazon warrior Shampoo hasn't given up on Ranma yet-only instead of killing him, she now wants to marry him! There's just a few obstacles in the way of their future happiness, starting with a childhood phobia of Ranma's that's very relevant when it comes to Shampoo. Then there's Shampoo's suitor Mousse, martial arts master of hidden weapons, and her formidable grandmother, Cologne.